Rhizospheric microbiomics integrated with plant transcriptomics provides insight into the Cd response mechanisms of the newly identified Cd accumulator Dahlia pinnata - Li, Xiong; Li, Boqun; Jin, Tao; Chen, Huafang; Zhao, Gaojuan; Qin, Xiangshi; Yang, Yongping; Xu, Jianchu (Frontiers in Plant Science, 2022)
Phytoremediation that depends on excellent plant resources and effective enhancing measures is important for remediating heavy metal-contaminated soils. This study investigated the cadmium (Cd) tolerance and accumulation characteristics of Dahlia pinnata Cav. to evaluate its Cd phytoremediation potential. Testing in soils spiked with 5–45 mg kg–1 Cd showed that D. pinnata has a strong Cd tolerance capacity and appreciable shoot bioconcentration (0.80–1.32) and translocation (0.81–1.59) factors, indicating that D. pinnata can be defined as a Cd accumulator. In the rhizosphere, Cd stress (45 mg kg–1 Cd) did not change the soil physicochemical properties but influenced the bacterial community composition compared to control conditions. Notably, the increased abundance of the bacterial phylum Patescibacteria and the dominance of several Cd-tolerant plant growth–promoting rhizobacteria (e.g., Sphingomonas, Gemmatimonas, Bryobacter, Flavisolibacter, Nocardioides, and Bradyrhizobium) likely facilitated Cd tolerance and accumulation in D. pinnata. Comparative transcriptomic analysis showed that Cd significantly induced (P < 0.001) the expression of genes involved in lignin synthesis in D. pinnata roots and leaves, which are likely to fix Cd2+ to the cell wall and inhibit Cd entry into the cytoplasm. Moreover, Cd induced a sophisticated signal transduction network that initiated detoxification processes in roots as well as ethylene synthesis from methionine metabolism to regulate Cd responses in leaves. This study suggests that D. pinnata can be potentially used for phytoextraction and improves our understanding of Cd-response mechanisms in plants from rhizospheric and molecular perspectives.